Industrial robotics - Cook, Jerome T.; Stauffer, Robert (Fundamental manufacturing processes)
Industrial robots are automated, flexible components used for a wide range of applications within manufacturing systems. This program covers the array of robot configurations and features segments on: key manufacturing applications using robots, rectangular arm robots, SCARA robots, articulated/jointed arm robots, end effector hand, or gripping devices, end effector tools, on-line & off- line robot programming, advantages and disadvantages of industrial robots.